How to speak dragonese - Cowell, Cressida (New York : Little, Brown and Co., 2010)
Recounts the further escapades of Hiccup Horrendous Haddock the Third as he continues his Viking training during which he escapes from a boatload of Roman soldiers and searches for his kidnapped dragon.
"First published in Great Britain in 2005 by Hodder Children's Books"--P. facing t.p.
980
Accelerated Reader AR
Keywords: Vikings -- Juvenile fiction; Dragons -- Juvenile fiction; Pirates -- Juvenile fiction